Developing multimodal interactional competence in EMI lecturers. Reflexive practice in an online international programme. - Querol-Julián, Mercedes (Routledge, 2025)
Literature reveals that teacher-student interaction in English-medium instruction (EMI) lectures is conspicuous by its absence. To repair this situation, scholars urge the implementation of student-centred approaches and claim the importance of using multimodal resources. Most research has focused on face-to-face environments, and little has explored digital ones. Live online teaching, nevertheless, may pose additional challenges in EMI since the multimodal strategies that aid learning and interaction in English in face-to-face classes work differently. Therefore, the shift from face-to-face to online teaching requires the development of EMI teachers’ multimodal interactional competence (MIC), i.e., multimodal literacy needed to foster and manage classroom interaction. The chapter introduces a pedagogy to develop EMI online lecturers’ MIC that favours their professional development through reflexive practice and aims to raise semiotic awareness in e-classrooms. Lecturers are involved in a personalised coaching process based on the guided observation and reflection of the video recordings of their lectures. After presenting the theoretical and methodological frameworks of the pedagogy, the case study of an EMI teacher involved in an online international MBA programme illustrates its design. Results of the effectiveness of its implementation are also presented.
Es un capítulo de: (2025). Querol-Julián, M., Fortanet-Gómez, I. (2025). Multimodal literacy in English as an additional language in higher education. Routledge
Keywords: EMI lecturers; multimodal literacy; online teaching; multimodal interactional competence; personalised coaching; reflexive practice